The Difference of Neiguan Acupressure Points (Pc6), Hypnotherapy, and Hypnopressure in Reducing Anxiety of Hemodialysis Patients - Hanung Prasetya; Sri Yatmihatun (Indonesian Journal of Medicine, 2023)
Background: The anxiety felt by patients undergoing hemodialysis can decrease the quality of life, cause a sleep disorder, and even aggravate the disease. Acupressure, hypnotherapy, or hypnopressure have minimal side effects and are easy to do in reducing anxiety. The study aims to analyze the different effects of acupressure, hypnotherapy, and hypnopressure in reducing anxiety in patients undergoing hemodialysis programs.Subjects and Method: It was an experimental study using a randomized controlled trial. It was conducted at Dr. Moewardi Hospital Surakarta, Central Java. The number of study subjects from March 2021 - July 2022 was 300 patients undergoing the hemodialysis program, with 75 subjects obtaining acupressure intervention, 75 subjects obtaining hypnotherapy intervention, 75 subjects obtaining hypnopressure intervention, and 75 subjects obtaining standard/control treatment. The sampling technique used was purposive sampling. The dependent variables in this study were acupressure, hypnotherapy, and hypnopressure, while the independent variable was the anxiety of patients who underwent a hemodialysis program for less than a year or less than 10 times. Anxiety was tested using the Hamilton Rating Scale for Anxiety questionnaire. Data analysis was conducted using an independent t-test, with the SPSS statistics program.Results: Post-acupressure anxiety score (Mean= 17.31; SD= 3.22) was lower than pre-acupressure (Mean= 23.17; SD= 2.68) and the result was statistically significant (p<0.001). Post-hypnotherapy anxiety score (Mean= 15.13; SD= 2.83) was lower than pre-hypnotherapy (Mean= 23.09; SD= 2.38), and the result was statistically significant (p<0.001). anxiety score after hypnopressure (Mean= 12.64; SD= 2.23) was lower than before hypnopressure (Mean= 23.13; SD= 2.53) and the result was statistically significant (p<0.001).Conclusion: Hypnopressure is more effective in lowering anxiety in patients undergoing a hemodialysis program.Keywords: anxiety, acupressure, hypnotherapy, hypnopressure, hemodialysisCorrespondence: Hanung Prasetya. Health Polytechnique of Health Ministry Surakarta. Jl. Letjend Sutoyo, Mojosongo, Surakarta 57127. Email: hanungprasetya168@gmail.com. Mobile: 08122638908Indonesian Journal of Medicine (2023), 08(01): 59-67https://doi.org/10.26911/theijmed.2023.08.01.06